Estrogen Receptor-Related DNA and Histone Methylation May Be Involved in the Transgenerational Disruption in Spermatogenesis by Selective Toxic Chemicals - Han, Xiao; Zhang, Pengfei; Shen, Wei; Zhao, Yong; Zhang, Hongfu (Frontiers in Pharmacology, 2019)
Air pollution is a global threat to human health especially spermatogenesis. Animal and epidemiological studies suggest that epigenetic factors can transmit the pathologies transgenerationally. Paternal epigenetic effects can greatly impact on the offspring health. In this study and together with our previous report, we found that H2S donor Na2S and/or NH3 donor NH4Cl diminished mouse fertility, decreased spermatozoa concentration and motility, and impaired spermatogenesis in three consequent generations (F0, F1, and F2). In current study, we found that DNA methylation, histone methylation, and estrogen receptor alpha (ER) were impaired by NH4Cl and/or Na2S in F0, F1 and F2 mouse testes. Moreover, NH4Cl and/or Na2S might act as environmental endocrine disrupting chemicals to decrease estrogen and testosterone in mouse blood. It has been reported that ER signaling is intertwined together with DNA methylation and histone methylation which plays very important roles in spermatogenesis. These data together indicate that the transgenerational disruption in spermatogenesis by NH4Cl and/or Na2S may be through ER related DNA methylation and histone methylation pathways. Therefore, we strongly recommend that greater attention should be paid to NH3 and/or H2S contamination to minimize their impact on human health especially spermatogenesis.